Sentido De Vida y Consumo De Alcohol En Estudiantes De Psicología de la Universidad Antonio Nariño de Bogotá 2015 (2015)
The objective of this research was to analyze the relationship between the meaning of life and consumption of alcohol in psychology students at the University Antonio Nariño in Bogota in the first half of 2015, differentiating the dimensions of life purpose and existential consistency and identity, as well as identify behavioral patterns of harmful drinking or risk. To effect this, under a -correlacional descriptive observational design and a probabilistic random sampling, 170 students with informed consent voluntarily responded Dimensional Sense of Life Scale (DSLS) and the test for the identification of disorders due to alcohol (AUDIT). They assessed the meaning of life and vital dimensions of existential purpose and Consistency also seeking alcohol level and pattern of intake of alcoholic beverages. To analyze the statistical package SPSS version 20.0 was used for Windows® statistic®.